(How) are decisions made in child and family social work supervisions?. (November 2022) - Webb, Joseph; Wilkins, David; Martin, Richard
Supervision is widely recognised as a core activity for social work. In this paper, we explore the nature of decision-making in supervision, using a collection of twelve audio-recordings from one child protection team in England. We apply Conversation Analysis to see how potential actions are put 'on the table', by whom, and the interactional work that occurs before any final decision is made. Within these data we find that supervision may not be an especially key site for decision-making. When actions are proposed, we identify three primary patterns: unilateral decision making, bilateral decision making and polar questions which instigate decision making sequences. In each, it is almost always the supervisor who proposes a possible future action, and the social worker who responds. If the social worker is agreeable, there is often little further discussion. When the social worker resists the proposal or there is further talk around the future action, the subsequent conversation was likely to focus on how it reflects on the worker's professional competence, rather than the merits of the action and implications for the family. These findings raise the question of how (and where) casework decisions are made in this social work team, if not in supervision. They also suggest we need to pay more attention to issues of professional standing and creating opportunities for shared decision making when thinking about supervision. Our analysis furthers current knowledge of what happens in social work supervision by demonstrating how epistemic and deontic domains, as well professional competency, are interactionally relevant forces shaping the decision-making process.